Energy and electricity consumption of the information economy sector in Finland - Kari Hiekkanen; Timo O. Seppäläinen; Ilkka Ylhäinen (The Research Institute of the Finnish Economy (ETLA), 2021)
The role of digital technologies is becoming increasingly important in our day-to-day life. Digital technologies have become part of our social life as well as business operations across different industrial and public sectors. Because of digitalization, the internet protocol and data traffic have been on the rise for several years. Several estimates of the growth in energy consumption of data networks and the information economy sector have been presented in recent years. Occasionally consumer behavior has been claimed to be behind of these increases in electricity use. This report analyzes the energy and electricity consumption of the Finnish information economy sector from 2011 until 2018. Additionally, we compare the Finnish electricity use to other European countries with similar data available. Our report shows that the energy efficiency of the technologies used in the information sector has not kept pace with the growth in the volumes of data transferred on fixed and mobile networks.
Keywords: L8; L82; L86; L94; 330; Information economy sector; ICT sector; IP traffic; Data usage; Energy consumption; Electricity consumption